1
$\begingroup$

Find how quickly $y$ converges to $y^*$ in the vicinity of the balanced growth path $$ y=Y/AL=f(k); \; y^*=f(k^*) $$ They suggest the hint, write $k=g(y)$, where $g(\bullet)=f^{-1}(\bullet)$.)

$Y$ is product output; $AL$ is effective labour; $K$ is capital; lowercase letters are divided by $AL$ (e.g. $y=Y/AL$); $k^*$ is the balanced growth path of capital.

This is problem $1.11$ in Advanced Macro by Romer. I have tried looking at Lagrange Inversion Theorem, and applying the above get to the first order Taylor series centered around $k^*$

$$ \displaystyle g(y) = k^* + \lim_{k \to k^*} \left( \frac{y-f(k^*)}{1!} \right) \frac{d^0}{dw^0} \left( \frac{k-k^*}{f(k)-f(k^*)} \right) $$

but since $y=f(k)$ and the zeroth derivative is the function itself, we get the following cancelation:

$$ = k^* + \lim_{k \to k^*} \frac{f(k)-f(k^*)}{f(k)-f(k^*)}(k-k^*) $$

$$ = k^* + \lim_{k \to k^*}(k - k^*) = k^* $$

Which doesn't tell us anything ... Do we need to look at the second order derivative?

$\endgroup$
3
  • $\begingroup$ Time as a variable does not appear in any of your equations. Perhaps you neglected to type in relevant information? $\endgroup$ – Giskard Jan 22 '16 at 10:33
  • $\begingroup$ Ahh, okay thank you, I think I have it now .. should I post the answer? $\endgroup$ – Sunhwa Jan 22 '16 at 15:41
  • $\begingroup$ If you have the time, sure! $\endgroup$ – Giskard Jan 22 '16 at 16:07
1
$\begingroup$

I believe there is a quicker way here. By the inverse function theorem, we have

$$y = f(k) \implies k = f^{-1}(y) = f^{-1}[f(k)] \implies \frac {\partial f^{-1}(y)}{\partial y} = \frac {1}{f'(k)}$$

Keeping all these relations in mind, we also have

$$\dot y = f'(k)\cdot \big[sf(k) - (n+g+\delta)\cdot f^{-1}(y)\big]$$

$$\implies \frac{\partial \dot y}{\partial y} \bigg|_{y=y^*} = \frac {\partial f'(k^*)}{\partial y}\cdot \big[sf(k^*) - (n+g+\delta)\cdot k^*\big]\\ + f'(k^*)\cdot \left[s - (n+g+\delta)\cdot \frac {1}{f'(k^*)} \right]$$

$$\implies \frac{\partial \dot y}{\partial y} \bigg|_{y=y^*} = 0 + sf'(k^*) - (n+g+\delta)$$

etc

$\endgroup$
1
  • $\begingroup$ Wow absolutely! Reading my answer again is so messy .. Thanks @Alecos_Papadopoulos ! $\endgroup$ – Sunhwa Jan 23 '16 at 4:25
3
$\begingroup$

Okay so, in the book they looked at the first order taylor series of $\dot{k}$, so as @denesp said, we need the time here too! So rather here we should look at the taylor series around $\dot{y}$

$$ \displaystyle \dot{y}(y) \simeq \left[ \frac{\partial \dot{y}(y)}{\partial y(k)} \bigg|_{y=y^*} \right] (y(k) - y(k^*)) $$

$$ \frac{\partial \dot{y}(y)}{\partial y(k)} \bigg|_{y=y^*} = \left( \frac{\partial \dot{y}(y)}{\partial k(t)} \bigg|_{y=y^*} \right) \left( \frac{\partial k(t)}{\partial y(k)} \bigg|_{k=k^*} \right) $$

First we look at:

$$ y=f(k) $$

$$\Rightarrow \dot{y} = \frac{d}{dt} f(k) = \frac{d f}{d k} \frac{dk}{dt} = f'(k) \dot{k} $$

We know the key equation of the Solow model is:

$$ \dot{k}(t) = s f(k(t)) - (n+g+\delta)k(t) $$

$$ \Rightarrow \dot{y} = f'(k) \left[ s f(k(t)) - (n+g+\delta)k(t) \right] $$

We take the derivative of this with respect to capital:

$$ \frac{\partial \dot{y}}{\partial k} = f''(k)\left[ s f(k(t)) - (n+g+\delta)k(t) \right] + f'(k) \left[ s f'(k) - (n+g+\delta) \right]$$

The value $k^*$ is the golden-rule level of the capital stock so:

$$ s f(k^*) = (n+g+\delta)k^* $$

And hence

$$ \left( \frac{\partial \dot{y}}{\partial k} \bigg|_{y=y^*} \right) = f''(k^*)*(0) + f'(k^*)\left[ s f'(k^*) - (n+g+\delta) \right] $$

Next we use the hint (not much of a hint, and rather misleading to begin with in my opinion)

$$ \left( \frac{\partial k(y)}{\partial y(t)} \bigg|_{k=k^*} \right) = \left( \frac{\partial y(k)}{\partial k(t)} \bigg|_{y=y^*} \right)^{-1} = f'(k^*)^{-1} = g'(y^*) $$

Plugging both of these in to our first order partial derivative:

$$ \frac{\partial \dot{y}(y)}{\partial y(k)} \bigg|_{y=y^*} = \left( f'(k^*)\left[ s f'(k^*) - (n+g+\delta) \right] \right) * \left( f'(k^*)^{-1} \right) $$

$$ = s f'(k^*) - (n+g+\delta) $$

since around the balanced growth path $s = (n+g+\delta)k^*/f(k^*)$ and putting

$$ - \frac{\partial \dot{y}(y)}{\partial y(k)} \bigg|_{y=y^*} = \lambda $$

$$ \lambda = (n+g+\delta) - \frac{(n+g+\delta)(k^*)*f'(k^*)}{f(k^*)} $$

With $\alpha_k = \frac{k*f'(k)}{f(k)} $ being the elasticity of output with respect to capital we obtain:

$$ \lambda = (n+g+\delta)(1-\alpha_k(k^*)) $$

So $y$ converges to its balanced growth-path value rate $\lambda$ the same as $k$ converges to $k^*$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.